A study on the grindability of portland cement clinker containing transition metal oxides - Tsivilis, S.; Kakali, G. (Cement and concrete research, 1997)
The subject of this paper is to investigate the effect of transition metal oxides on the grindability of clinker. As it is concluded clinker containing ZnO has the lower grindability while clinker containing MnO or Cr 2O 3 has the higher grindability. The classification of the added oxides, concerning the clinker grindability (descending sort), is: MnO, Cr 2O 3, Ni 2O 3, ZrO 2, CuO, Co 2O 3, V 2O 5, MoO 3, TiO 2, ZnO. The study of the clinker by means of X-Ray diffraction and optical microscopy confirms the results.